2013
DOI: 10.1177/0042085913481361
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Profiles of Preservice Teachers With Different Levels of Commitment to Teaching in Urban Schools

Abstract: Understanding the beliefs of preservice teachers is an important area to investigate in the teacher education process. This article examines the relationship between preservice teachers' beliefs pertaining to diversity and urban schooling and how these inclinations contribute to a commitment to teaching urban students. Canonical correlation analysis was used to identify profiles of preservice teachers who exhibited varying degrees of interest to teach in urban schools. The statistical analysis provides a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 62 publications
(105 reference statements)
1
19
0
Order By: Relevance
“…Several patterns documented in the literature suggest conditions that lend themselves to the development of such a commitment. For example, when teacher-candidates express a stronger sense of value for both multiculturalism and social justice as tenets of their teaching approach, they report a stronger desire to teach in an urban setting (Aragon et al, 2014). In addition, teacher-candidates who experience student teaching placements in urban settings are more likely to accept an initial teaching position in a city school (Krieg, Theobald, & Goldhaber, 2016).…”
Section: Preparing Urban Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several patterns documented in the literature suggest conditions that lend themselves to the development of such a commitment. For example, when teacher-candidates express a stronger sense of value for both multiculturalism and social justice as tenets of their teaching approach, they report a stronger desire to teach in an urban setting (Aragon et al, 2014). In addition, teacher-candidates who experience student teaching placements in urban settings are more likely to accept an initial teaching position in a city school (Krieg, Theobald, & Goldhaber, 2016).…”
Section: Preparing Urban Teachersmentioning
confidence: 99%
“…One challenge in preparing preservice teacher-candidates for urban teaching careers is to foster interest in urban teaching and support the evolution of such interest into a long-term commitment to such work. Often, preservice teachers indicate an initial preference toward teaching children from a background similar to their own (Groulx, 2001) and in a school setting similar to the one that they experienced (Aragon, Culpepper, McKee, & Perkins, 2014; Chisholm, 1994; Easter, Shultz, Neyhart, & Reck, 1999; Shultz, Neyhart, & Reck, 1996).…”
Section: Teacher Preparation For Urban Contexts and Social Justice Endsmentioning
confidence: 99%
“…She wanted to explore traditional cultures of Africa to inspire elementary Black students to recognize their rich heritage. The third author, the White teacher hosting this special enrichment project, has chosen to teach in an urban district because of her positive professional commitment (Aragon, Culpepper, McKee, & Perkins, 2014) to recognizing and supporting students of color in enrichment and gifted programs.…”
Section: Participantsmentioning
confidence: 99%
“…Effective teachers of students living in poverty hold high expectations for all students and explicitly tell students they are capable of learning (Zeichner, 2005). Furthermore, what teachers believe about their students has serious implications for the quality of instruction students receive, as research has shown that teachers' beliefs play a powerful role in influencing instructional practices (Aragon, Culpepper, McKee, & Perkins, 2013;Bryan & Atwater, 2002;Jordan & Stanovich, 2003). In other words, teachers who believe all students are capable of learning are more likely to provide all students with effective instruction.…”
Section: Introductionmentioning
confidence: 99%